2019
DOI: 10.30919/esee8c353
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Spin Caloritronic Devices

Abstract: We report a concept of thermoelectric devices, cooperative spin caloritronics device (CSCD), where cooperation between two or more energy channels such as spin, charge and heat currents can significantly enhance energy efficiency of spin caloritronic devices. We derive the figure of merit and the maximum efficiency due to cooperative effect in analytic forms for a CSCD. Cooperative effects significantly improve the figure of merit and the maximum efficiency in spin caloritronic systems with multiple couplings … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Although much excellent work has been devoted to studying the effects of electron–phonon [ 47 , 48 ], electron–photon [ 49 ], and electron–electron [ 50 , 51 , 52 , 53 ] interactions on thermoelectric transport, discussions of thermoelectric transistors and diodes in a strong coupling regime are still lacking. In this work, we investigated the inelastic thermoelectric transport in a single QD that was strongly coupled to photons residing inside a microwave cavity [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Strong or even ultra-strong couplings provide a great avenue for realizing novel quantum devices.…”
Section: Introductionmentioning
confidence: 99%
“…Although much excellent work has been devoted to studying the effects of electron–phonon [ 47 , 48 ], electron–photon [ 49 ], and electron–electron [ 50 , 51 , 52 , 53 ] interactions on thermoelectric transport, discussions of thermoelectric transistors and diodes in a strong coupling regime are still lacking. In this work, we investigated the inelastic thermoelectric transport in a single QD that was strongly coupled to photons residing inside a microwave cavity [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Strong or even ultra-strong couplings provide a great avenue for realizing novel quantum devices.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the rise of mesoscopic thermoelectrics has partially revived the study on heat transport in mesoscopic systems [28][29][30][31][32][33][34]. The thermoelectric effect, which enables the conversion of heat into electricity and vice versa, can be exploited to harvest waste heat and covert the heat to useful electric power [35], Highly efficient thermoelectric devices require salient control over heat and charge conduction [36][37][38][39]. With the knowledge of mesoscopic physics, it may be possible to harness heat and charge transport in unprecedented ways.…”
Section: Introductionmentioning
confidence: 99%
“…The study of thermoelectric transport at nanoscales 1-5 is important at least for two reasons. First, it is a realm where mesoscopic fluctuations and dissipations work together with quantum mechanics [6][7][8][9][10][11][12][13][14][15][16][17][18] . Second, nanostructured materials are important routes toward high thermoelectric efficiency and power, as motivated by the seminal works of Hicks and Dresselhaus [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Second, nanostructured materials are important routes toward high thermoelectric efficiency and power, as motivated by the seminal works of Hicks and Dresselhaus [19][20][21][22] . While most of the studies are based on elastic transport processes, recent researches found that inelastic transport processes lead to phenomena that have not been found in elastic transport 16,[23][24][25][26][27][28][29] . The first example is the cooling by heating effect in three-terminal (i.e., two electronic electrodes and a bosonic terminal) thermoelectric transport where one of the two electronic reservoirs can be cooled (the other one heated) by heat injection from the bosonic reservoir [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%